Implementation of the Pan-European Approaches to Property Taxation in Ukraine - Havrylyuk, Ruslana (Institute for Local Self-Government Maribor, 2021)
The world experience of real estate taxation supports the view that the tax base should be the "market value" of the object of real property with a simultaneous provision for a certain minimum level of this value which is not subjected to taxation. However, this only works only if there is a healthy, active and comprehensive property market for all types of properties across the entire country. Until such a market exists, "market value" as defined, is a goal to be aimed at. This will complement the fiscal function of real property tax with an extremely important function, being the social redistribution of wealth from the rich to the poor. An extremely important factor in the low efficiency of real estate taxation still remains, and this is the excessive centralisation of political power in Ukraine and the underdevelopment of local and regional self-governments As a result the latter are deprived of their potential to provide services to their citizens, and at the same time they have no incentive to generate public funds to ensure their financial resources. For this reason, the declared decentralisation of power in Ukraine is arch-necessary.
Keywords: property tax; immovable property tax; valuation; tax reform